PERBEDAAN SENSASI NYERI MENGGUNAKAN AROMATERAPI BUNGA MAWAR DENGAN TEKNIK NAFAS DALAM TARHADAP TINGKAT NYERI PERSALINAN KALA 1 - AINAL MARDIAH UFDK (HUMAN CARE JOURNAL, 2020)
Childbirth is the process of spending the results of conception in the womb through the birth canal. The labor process begins with uterine contractions causing cervical thinning and pain response. One of the efforts to reduce pain is non-pharmacology. This study aimed to determine The Difference Pain Sensation of Rose Aromatherapy and Breath Technique toward the First Stage Active Labor Pain Level in BPM R Bukittingi. This study used quasy experimental with post-test design only design non-equivalent group. It was conducted on July 2019. 20 people were chosen as the samples. They had been chosen by using accidental sampling. Then, it was analyzed by mann whitney test. The results of this study showed that the average level of labor pain in the active phase I by using rose aromatherapy was 1.60 (moderate pain).  Then, the average level of labor pain by using rose flower aromatherapy with deep breath technique was.9000 (mild pain) with (p=014 <0.05). From the results of the study, it can be showed that there are differences in the level of labor pain by using rose aromatherapy and deep breath techniques. For this reason, it is hoped that all parties improve services to maternity. One of them is by providing rose flower aromatherapy with deep breath technique that may reduce the level of labor pain during the active phase.Keywords             : Pain Level, Rose Aromatherapy, Deep Breath Technique